Scaling and branching in wet sonogels as a function of the volume fraction of the liquid phase - Vollet, D. R. [UNESP]; Donatti, D. A. [UNESP]; Ruiz, Alberto Ibanez [UNESP] (Iop Publishing Ltd, 2009)
The structural properties of wet silica sonogels prepared with different volume fractions of the liquid phase were studied by small-angle x-ray scattering (SAXS) and thermogravimetry (TG). The SAXS intensity curves of aged wet gels were all found to be well fitted by the form factor for scattering from non-randomly branched polymers in solution. The radius of gyration (R(g)) of the polycondensates and the branching density were found to increase with the volume fraction of the liquid phase of the wet gels. The molecular weight (M) of the branched polycondensates was found to scale as M similar to R(g)(alpha) with alpha quite close to 2 in the studied range.